Design Optimization and Testing of Electric Tire Patching Tool with Grip Pliers - Azzuhri, Ahmad Darmawan; Wijianto, W; Siswanto, Waluyo Adi (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2024)
The tire patching station is become a major need in this country. Based on this situation, many people are interested to observe about Tire Patching Tool that basically combines a heating and a pressing component. The interests to observe this tool are turned up besides it can be a motivating study, it also provide an opportunity to carry out a business field. Likewise here, it motivated to optimize the design that has created before using optimization method. This research has two major aims that are redesign the better tire patching tool to maximize its benefits and test the performance of the product and examine the cost if the tool wishes to be mass produced. Two designs of the tire patching tool in this project will be evaluated using Solidworks 2013 program. The evaluation is stated in the simulation of statics study. In the simulation, both of them will be loaded by 200 N, 400 N, 600 N, 800 N, 1000 N and 1200 N. These load variation are used to indicate the stress distributions, displacements and safety factors of the product. Then, the known terms will generate a visualization of most carrying load on the product structure so the possibility of fatigue can be checked. The result of research concludes that there are some improvements of tool performances. In the other hand the cost of production is also reported so it can become a reference to do the further works.